Composição nutricional do Leite UHT (Ultra High Temperature) comercializado em Parintins-AM - Albuquerque, Tacio Melo (Brasil, 2024)
The aim of this study was to characterize the quality of UHT milk sold in Parintins-AM, by means of its nutritional composition. Were realized of 715 samples of UHT milk sold in Parintins-AM were analyzed for protein, fat and lactose. The analyses were carried out at the Laboratory of the Milk Management Program for the North and Northeast Regions, located in the Zootechnics Department of the Federal Rural University of Pernambuco, in accordance with Normative Instruction No. 76 and 77, using Bentley® equipment. The results obtained were stored in the database of the Amazonas Milk Extension Program: producing milk with sustainability and showed results for Protein, Fat and Lactose that are in line with the minimum quality values of the Technical Regulations for UHT Milk.